2007
DOI: 10.1021/bi700454x
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminal A Domain of Staphylococcus aureus Fibronectin-Binding Protein A Binds to Tropoelastin

Abstract: Staphylococcus aureus is an important human pathogen. Its virulence factors include a variety of MSCRAMMs (microbial surface component recognizing adhesive matrix molecules), each capable of binding specifically to the host extracellular matrix. The fibronectin-binding protein, FnBPA, has been shown previously to bind immobilized fibronectin, fibrinogen, and alpha-elastin peptides. Here we show that region A of FnBPA (rAFnBPA) binds to recombinant human tropoelastin. Binding occurs to three separate truncates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…Our results indicated that all recombinant truncated human tropoelastin fragments (GST-HTE(1-18), GST-HTE (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), GST-HTE (27)(28)(29)(30)(31)(32)(33)(34)(35)(36), and GST-HTE(27-28)) bind to M. tuberculosis Ag85B with similar K D values (ϳ0.5 M) (Figs. 2B and 3B).…”
Section: Discussionmentioning
confidence: 69%
“…Our results indicated that all recombinant truncated human tropoelastin fragments (GST-HTE(1-18), GST-HTE (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), GST-HTE (27)(28)(29)(30)(31)(32)(33)(34)(35)(36), and GST-HTE(27-28)) bind to M. tuberculosis Ag85B with similar K D values (ϳ0.5 M) (Figs. 2B and 3B).…”
Section: Discussionmentioning
confidence: 69%
“…In their study, Bisognano et al showed that LexA is a repressor of fnbB expression, and consequently, SOS response induction by commonly used fluoroquinolones resulted in the increased expression of the FnBPB protein on the bacterial surface (7). As FnBPs have been shown to play an important role during invasion of mammalian cells (47,48) and in mediating adherence to different host extracellular matrix components, such as fibronectin, fibrinogen, elastin, or tropoelastin (23,43,55), an adverse consequence of SOS induction by antibiotics would be that it might facilitate colonization of host cells and medical implants (13,17). Accordingly, our results suggest that an increase in FnBPB expression through activation of the SOS response is sufficient to induce a noticeable increase in the capacity of the strain to produce multicellular communities on abiotic surfaces in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…During the major phase of elastogenesis, multiple tropoelastin molecules associate through coacervation (30 -32). Because of the abundance of elastin or tropoelastin on the surface of host cells, several bacterial MSCRAMMs use elastin and/or tropoelastin to mediate adhesion during the infection process (33)(34)(35).…”
mentioning
confidence: 99%